Transforming Urban Water Supplies in India : the Role of Reform and Partnerships in Globalization. - Gopakumar, Govind (Routledge contemporary South Asia series., 2011)
The absence of water supply infrastructure is a critical issue that affects the sustainability of cities in the developing world and the quality of life of millions of people living in these cities. Urban India has probably the largest concentration of people in the world lacking safe access to these infrastructures. This book is a unique study of the politics of water supply infrastructures in three metropolitan cities in contemporary India -- Bangalore, Chennai and Kochi. It examines the process of change in water supply infrastructure initiated by notable Public Private Partnership's effort.